(untitled) (Bangladesh Journal of Medical Science, 2012)
Objectives: The purpose of this study to assess the effect of oligohydramnios on perinatal outcome especially at third trimester of pregnancy. Methods: This prospective and observational study was conducted in a private specialized hospital at Dhaka city from January to December 2009. In this study 78 singleton pregnant females with gestational age from 28 - 42 weeks with less amniotic fluid index (AFI) were analyzed for perinatal outcome. Data were expressed as number (percentage). Proportion test was performed for comparison between two groups , P value <0.05 was taken as level of significance. Results:Women with oligohydramnios were significantly associated with an abnormal antepartum fetal heart rate (FHR), meconium stained fluid, Apgar score less than 7 or NICU admission. Also subjects with AFI of 5.0 cm or less had a higher rate of cesarean section for fetal distress. Conclusions: Antepartum oligohydramnios is associated with an increased risk of fetal heart rate abnormalities. Although in our population it is not predictive of adverse perinatal outcome as measured by low apgar score and NICU admission, yet this may be reflective of the aggressive antepartum and intrapartum management that these patients received. DOI: http://dx.doi.org/10.3329/bjms.v11i1.9820 BJMS 2012; 11(1): 33-36